Cross-curricular Connections of Music Culture and Other Subjects in Croatian Elementary Schools - Begić, Amir; Šulentić Begić, Jasna; Vodopić, Ivan (Revija za elementarno izobraževanje, 2023)
Music lessons provide many opportunities for cross-curricular connections with other subjects. As part of the work, research was conducted on a sample of 110 teachers who teach Music Culture in elementary school. The aim of the research was to find out the teachers' views on the implementation of cross-curricular connections between the teaching of Music Culture and other subjects, the frequency and methods of conducting such teaching, as well as possible statistically significant differences between teachers in the attitudes and implementation of cross-curricular connections with regard to sociodemographic variables. We believe that the results of this research indicate the need for more intensive implementation of cross-curricular connections between the teaching of Music Culture and other subjects.
Keywords: teaching of Musical Culture, cross-curricular connection, interdisciplinarity, elementary school